Back Cover: Structure–Activity Relationships of Quinoxaline‐Based 5‐HT3A and 5‐HT3AB Receptor‐Selective Ligands (ChemMedChem 6/2013). Issue 6 (24th May 2013) - Thompson, Andrew J.; Verheij, Mark H. P.; van Muijlwijk‐Koezen, Jacqueline E.; Lummis, Sarah C. R.; Leurs, Rob; de Esch, Iwan J. P.
<x xml:space="preserve">Abstract</x> The back cover picture shows the extracellular domains of two of the five subunits that make up a 5‐HT3 receptor. Quinoxalines (general structure shown) bind with reasonable potency to this receptor, probably at the orthosteric binding site located between two adjacent subunits. Through modifications to the functional groups at the R1, R2 and R3 positions, the ability of these ligands to distinguish between homomeric 5‐HT3AR and heteromeric 5‐HT3AB receptors was probed. For more details, see the Full Paper by Sarah C. R. Lummis et al. on p. 946 ff.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>